The relationship between frequent premature ventricular complexes and epicardial adipose tissue volume - Wang, Zhe; Jiao, Siqi; Chen, Jiawei; Guo, Hehe; Ren, Lichen; Sun, Liping; Sun, Yihong; Chen, Yingwei (Frontiers in Endocrinology, 2023)
Background: Epicardial adipose tissue (EAT) is related to atrial fibrillation. The association between EAT volume and premature ventricular complexes (PVCs) remains unclear. Our study aimed to investigate the effect of EAT volume on the risk of frequent PVCs and burden levels of PVCs.Methods: This observational study retrospectively recruited consecutive patients consulted between 2019 to 2021 at the First Affiliated Hospital of Zhengzhou University. Frequent PVCs patients (n=402) and controls patients (n=402) undergoing non-contrast computed tomography (CT) were enrolled. We selected evaluation criteria for the conduct of a 1:1 propensity score matching (PSM) analysis. Multivariable logistic analysis was used to investigate factors related to frequent PVCs. Furthermore, determinants of EAT volume and the burden levels of PVCs were evaluated.Results: Patients with PVCs had a significantly larger EAT volume than control patients. EAT volume was significantly larger in PVCs patients with men, BMI ≥ 24 kg/m 2 , diabetes mellitus, and in those with an E/A ratio < 1 PVCs patients. EAT volume was independently associated with PVCs. Moreover, the larger EAT volume was an independent predictor for the high burden level of PVCs. We revealed that the risk of high PVCs burden level was increased with the rising of EAT volume by restricted 3 / 21 cubic splines. Conclusions: EAT volume was larger in frequent PVCs patients than in control patients, regardless of other confounding factors. A large EAT volume was independently associated with high burden levels of PVCs. EAT volume may be a new mechanism to explain the pathogenesis of PVCs.